Reliability and validity of the Automatic Cognitive Assessment Delivery (ACAD) - Di Rosa, Elisa; Hannigan, Caoimhe; Brennan, Sabina; Reilly, Richard; Rapčan, Viliam; Robertson, Ian (Frontiers in Aging Neuroscience, 2014)
In this study we evaluated reliability and validity of the Automatic Cognitive Assessment Delivery (ACAD): a short computerised battery composed by memory and attention tests, delivered online and designed primarily for the elderly. Reliability was examined with a test-retest design and validity was assessed by means of comparison with standard neuropsychological tests. Older (N=32) and young adult participants (N=21) were involved. We found that the ACAD is free from any practice effect. Test–retest reliability was confirmed via significant correlations and high percentage agreements between the scores of three repeated assessments. ACAD scores were lower for older than for young adult participants, and correlated significantly with the standardised measures of memory and attention. Results demonstrate that the ACAD battery provides a reliable and valid measure of both immediate and delayed recognition memory and sustained attention, and may be useful for convenient and efficient cognitive assessment and monitoring in older adults.